Fault diagnosis of planetary gearboxes based on bispectral composite spectral features of torsional vibration modulation signals - ZHANG Yibao; HU Lei; XU Yuandong; SONG Xinkai (Jixie chuandong)
ObjectiveCompared with the linear vibration signal, the planetary wheel torsional vibration signal is not affected by the planetary wheel passing effect and the signal transmission path, and the spectral structure is simpler. Therefore, it is expected to get better diagnosis results based on the torsional vibration signal for planetary gearbox fault diagnosis. A new method for planetary gearbox fault diagnosis based on modulation signal bispectrum (MSB) analysis of torsional vibration signals was proposed.MethodsFirstly, the instantaneous speed signal was solved by the Hilbert transform method for the encoder signal. Secondly, the instantaneous speed signal was analyzed by MSB and the optimal carrier band was searched. Finally, the MSB optimal carrier band composite spectrum was constructed for the selected optimal carrier band as a fault diagnosis feature of the planetary gearbox.ResultsThe test results demonstrate that the proposed method can more intuitively reflect the fault state of the planetary wheel as well as the fault information, which verifies the effectiveness and superiority of the method in the planetary wheel fault diagnosis.